Segregation or Inclusion: An Experimental Study of the Psychological Support in the Professional Training for Persons with Disabilities - T.I. Bonkalo; S.V. Shmeleva; V.P. Kartashev; Kh.A. Sabanchieva (Moscow State University of Psychology and Education, 2024)
The article reveals the degree of effectiveness of segregated and inclusive forms of psychological and pedagogical support for students with special educational needs. In the psychological experiment took part 68 students with disabilities, its purpose was to identify the dynamics of the psychological well-being of the students depending on the inclusive or segregated forms of psychological trainings they took part in. As a result of the study, carried out with the help of the Scale of psychological well-being K. Riffe (adaptation of T.D. Shevelenkova, T.P. Fesenko), questionnaire Life Style Index (Plutchik, Kellerman, & Conte, 1979) and the methodology of SUN (V.A. Doskin, N.A. Lavrentieva, V.B. Sharay), we found out the differences between the groups of students according to their mood (t=7.55; p<0.001), well-being (t=4.89; p<0.001), activity (t=4.78; p<0.001), psychological well-being (t=4.65; p<0.001), tension of psychological defenses (t=2.27; p<0.05). These factors indicate the negative dynamics of psychological well-being of students with disabilities who studied in segregated groups with no conditionally healthy students. Based on the results of the psychological experiment, we made a conclusion, that the segregation of students with disabilities from other students is inexpedient, even if the purpose was providing them with psychological assistance in higher education.